Biodeterioration of Polyethylene High Density by Aspergillus versicolor and Aspergillus terreus - Vishnu Singh (Journal of Advanced Laboratory Research in Biology, 2012)
The present article investigates the biodeterioration ability of polyethylene high density by Aspergillus versicolor and Aspergillus terreus. Shake flask incubation for 30 days was done for the purpose of biodeterioration of polyethylene high density. The observations were recorded for initial and final dry weight of polyethylene high density before and after incubation in the culture medium were compared the percentage of biodeterioration of polyethylene. The strongest ability was observed by Aspergillus terreus with 7.59% biodegradability followed by Aspergillus versicolor with 3.79% of biodegradability. In conclusion, Aspergillus terreus was found to be efficient organism that degraded the polyethylene high density with maximum biodegradability as compared to Aspergillus versicolor.